A Mechanistic Study of Ni‐catalyzed Carbon Dioxide Coupling with Ethylene towards the Manufacture of Acrylic Acid. Issue 3 (20th February 2014) - Yang, Gang; Schäffner, Benjamin; Blug, Matthias; Hensen, Emiel J. M.; Pidko, Evgeny A.
Abstract The reaction mechanism of CO2 coupling with C2H4 by homogeneous Ni‐complexes bearing bidentate phosphorous ligands was studied by means of density functional theory calculations. The reaction is initiated by sequential coordination of C2H4 and CO2 to the Ni center, followed by a facile coupling step, which results in a stable nickelalactone intermediate. Subsequent decomposition of this intermediate through β‐H transfer is the rate‐determining step. Together with the following reductive elimination step to form acrylic acid they represent a strongly kinetically‐hampered process. Destabilization of the nickelalactone intermediate in the presence of large bite angle bidentate ligands has only a minor effect on the overall reaction energetics. Modifying the electronic properties of ligands is also not effective to drive the reaction in a catalytic manner. These studies indicate that the coupling reaction has to be enforced through an alternative route. It is predicted here that a base‐assisted decomposition of the nickelalactone intermediate represents a favorable reaction channel. The factors affecting the reactivity of this route are investigated. The best reactivity corresponds to the CH3OH‐solvated CH3ONa that allows the β‐H transfer step to proceed with a barrier of only 49 kJ mol−1.